The crystal structure of (N-([1,1′:4′,1″-terphenyl]-4,4′-diethyl)-2-(bis(pyridin-2-ylmethyl)amino)acetamide-κ4N,N,N″, O)tri(nitrato-kO, O′) samarium(III) - methanol - acetonitrile (1/1/1), C40H39SmN8O14 - Wang Hai-Ping; Zhang Ci-Mao; Huang Guo-Peng; Liang Jia-Jun (Zeitschrift für Kristallographie - New Crystal Structures)
C40H39SmN8O14, triclinic, P1̄ (no. 2), a = 8.2799(1) Å, b = 16.6666(5) Å, c = 17.1471(3) Å, α = 73.549(2)∘$73.549{(2)}^{° }$, β = 89.123(1)∘$89.123{(1)}^{° }$, γ = 83.045(2)°, V = 2252.2(1) Å3, Z = 2, Rgt${R}_{gt}$ (F) = 0.0592, wRref$wR_{ref}$ (F2) = 0.1438, T = 297.71(13) K.